Instagram and Communication of Leaders in Times of Crisis: Analysis of Instagram Account Framing @aniesbaswedan during the Covid-19 Pandemic - Rahmanto, Andre Noevi (Jurnal Politik Indonesia: Indonesian Political Science Review, 2023)
Leaders must be able to provide accurate and precise information so that it reaches the public—crisis leadership communication as a control in reducing the impact of the spread and panic of Covid-19.Purpouse: The focus of this article is on leadership communication in times of crisis. The method used in this study is a qualitative analysis of Robert N. Entman's framing model. The research object used is Anis Baswedan's Instagram account as a regional leader. This research was conducted at the start of the Covid-19 pandemic, from March to May 2020. Researchers collected all uploaded information on Anis Basedan's Instagram account and analyzed it using Robert N. Erman's four analytical knives, namely; Define Problems, Diagnose Causes, Make Moral Judgments, Treatment Recommendations. Based on the results of the framing analysis, Anis Baswedan's leadership communication during the Covid-19 pandemic 1) Define Problem, namely; Covid-19 transmission; The need for Health Facilities and Personnel; Social assistance; Covid-19 Education and Information; PSBB rules; Government Readiness. 2) Diagnose Causes namely; Spread of viruses; Community concern and increasing number of victims; Emergency Response and PSBB Violations; Appreciation of health workers; Economic Decline. 3) Make moral judgment: Government's responsibility; protect citizens; Cooperation and collaboration of all parties; Enforcement of discipline; Appreciation. 4) Treatment Recommendations namely; Discipline rules and health protocols; Limitation of activities, distribution of assistance; Information updates. The communication style used by Anis Baswedan is due to the situational factors of the Covid-19 pandemic, namely directive leadership communication.